ByzRev 07.2025.041: Epiphanios the Monk: Life of Mary, the Theotokos, and Life and Acts of St Andrew the Apostle.: Introduction, translation and commentary by Mary B. Cunningham (Translated Texts for Byzantinists 13). Liverpool: Liverpool University Press 2024. - Huggins, Mark (The Byzantine Review, 2025)
Epiphanios the Monk: Life of Mary, the Theotokos, and Life and Acts of St Andrew the Apostle. Introduction, translation and commentary by Mary B. Cunningham (Translated Texts for Byzantinists 13). Liverpool: Liverpool University Press 2024. xi+195 pp. – ISBN 978-1-80207-853-4